A Proposal to Revise the Histopathologic Grading System of Early Oral Tongue Cancer Incorporating Tumor Budding. (May 2019) - Elseragy, Amr; Salo, Tuula; Coletta, Ricardo D.; Kowalski, Luiz P.; Haglund, Caj; Nieminen, Pentti; Mäkitie, Antti A.; Leivo, Ilmo; Almangush, Alhadi
Abstract : The World Health Organization (WHO) grading system has a low prognostic value for early-stage oral tongue squamous cell carcinoma; greater prognostic power has been shown with tumor budding analysis. In this study, we combined tumor budding analysis with histopathologic grading according to WHO 2017. In our proposal, a revised grade I tumor is defined as a "well differentiated cohesive tumor"; revised grade II as a "moderately differentiated and/or slightly dissociated tumor"; and revised grade III as a "poorly differentiated and/or dissociated tumor." We evaluated the prognostic value of this proposed grading system in a multicenter cohort of 311 cases of early oral tongue squamous cell carcinoma. The proposed grading system showed significant prognostic value in multivariable analysis for disease-specific survival with a hazard ratio of 3.86 and a 95% confidence interval of 1.36-10.9 ( P =0.001). For disease-free survival, the proposed grading system showed good predictive power in multivariable analysis (hazard ratio, 2.07; 95% confidence interval, 1.00-4.27; P =0.009). The conventional WHO grading system showed a low prognostic value for disease-specific survival and disease-free survival ( P >0.05). In conclusion, the prognostic power of the WHO histopathologic grading improved significantly with incorporation of tumor budding. Our proposed grading system can be easily included in pathology reports.